2015
DOI: 10.1103/physreva.91.063839
|View full text |Cite
|
Sign up to set email alerts
|

Frequency comb generation in quadratic nonlinear media

Abstract: We experimentally demonstrate and theoretically explain the onset of optical frequency combs in a simple cavity-enhanced second-harmonic-generation system, exploiting second-order nonlinear interactions. Two combs are simultaneously generated around the fundamental pump frequency, with a spectral bandwidth up to about 10 nm, and its second harmonic. We observe different regimes of generation, depending on the phase-matching condition for second-harmonic-generation. Moreover, we develop an elemental model which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
161
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(169 citation statements)
references
References 60 publications
8
161
0
Order By: Relevance
“…However, if a particular second-order process dominates the dynamics, the problem can be greatly simplified by introducing a set of distinct field envelopes with widelyspaced carrier frequencies. For the particular case of secondharmonic generation (SHG) in high-finesse cavities, where frequency combs have been experimentally observed [14], the second-harmonic field is found to be dynamically slaved to the fundamental field, with the latter evolving according to the following mean-field equation [15], [16]:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, if a particular second-order process dominates the dynamics, the problem can be greatly simplified by introducing a set of distinct field envelopes with widelyspaced carrier frequencies. For the particular case of secondharmonic generation (SHG) in high-finesse cavities, where frequency combs have been experimentally observed [14], the second-harmonic field is found to be dynamically slaved to the fundamental field, with the latter evolving according to the following mean-field equation [15], [16]:…”
Section: Resultsmentioning
confidence: 99%
“…Although all microresonator frequency comb studies to date have revolved around third-order Kerr nonlinear effects, recent studies in macroscopic, free-space cavities have shown that similar phenomenologies can also manifest themselves in quadratically nonlinear cavities [13], [14]. In particular, experiments have shown that, similarly as for Kerr cavities, a cw laser coupled into a quadratically nonlinear cavity can transform into a frequency comb [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to generate optical frequency combs (OFCs), the use of passive nonlinear cavities has been shown to represent an attractive alternative to traditional techniques based on femtosecond mode-locked lasers. Indeed, comb generation has been demonstrated to occur in continuosly pumped resonators with third-or second-order nonlinearities [1,2]. In cavities dominated by the second-order nonlinerity, OFCs can be generated when the nonlinear crystal is phase-matched for second harmonic generation and the cavity is pumped above the threshold of the so-called internally-pumped optical parametric oscillation [2,3].…”
Section: Maurizioderosa@inoitmentioning
confidence: 99%
“…Indeed, comb generation has been demonstrated to occur in continuosly pumped resonators with third-or second-order nonlinearities [1,2]. In cavities dominated by the second-order nonlinerity, OFCs can be generated when the nonlinear crystal is phase-matched for second harmonic generation and the cavity is pumped above the threshold of the so-called internally-pumped optical parametric oscillation [2,3]. Here, we experimentally demonstrate, for the first time to the best of our knowledge, that quadratic frequency combs can be directly generated in a cw-pumped, nearly degenerate, doubly resonant optical parametric oscillator (OPO).…”
Section: Maurizioderosa@inoitmentioning
confidence: 99%